A Review: Factors Affecting RFID Adoption on E-Commerce Supply Chain of Bangladesh - Aslam, S.M. Tanzil; Wahid, Rosni Binti Abdul (International Journal of Membrane Science and Technology, 2023)
In Bangladesh e-commerce is getting more popular with the technological development like RFID. RFID is not a new technology but still Bangladesh can’t utilize of this technology and even RFID based distribution system. RFID technology could make business value in different levels of supply chain management. Many world-famous brands established their production house in Bangladesh mainly readymade garments, leather goods, textile, and energy-related companies, for the low production and low labor cost. Bangladesh is a late candidate in the e-commerce industry, and it is getting tremendous popularity within a short period. Bangladesh is a growing technological nation and trying to implement innovative technology in every sector. RFID technology has an excellent opportunity to explore Bangladesh’s business industry, especially for e-commerce based supply chain networks. All this literature examined the structure of RFID and its related factors. I this chapter, exiting literature associated with the factors affecting RFID adoption in e-commerce supply chain management in Bangladesh has been presented. Key elements such as technological, organizational, and environmental factors that influence RFID adoption are highlighted. The benefits and advantages of this technology implementation in the supply chain network in Bangladesh are also explained.